Negative Effects of Noise Pollution in Agriculture – A Review - Mihai CHITOIU; Georgiana MOICEANU; Gigel PARASCHIV (Communications of International Proceedings, 2020)
A problem not often discussed or recognized is represented by noise injury in agriculture. The recommended level of noise is not respected thus many workers, farmers or family members are exposed to it. Thus, these people experience hearing losses more often than people with other types of jobs. Just lately, an interest in the subject is mentioned also in the Occupational Health and Safety regulations. The main objective of this study was to review negative effects of noise pollution in agriculture in regard to the farmers interests toward protecting their workers and the safety measures they have taken to prevent health problems. The paper focuses on agriculture noise pollution since it is a very important sector in Europe that should be investigated and developed more and more. The findings are expected to enhance the understanding of noise pollution in agriculture and review different ways to prevent it.
Keywords: Noise Pollution; Agriculture; Protection Measures.